INFLUENCE OF SEED TUBE CURVATURE ON SEED LONGITUDINAL DISTRIBUTION - Savi,Daniel (2020)
ABSTRACT Studies on the longitudinal distribution of seeds in the sowing row seek to improve crop homogeneity, thus generating high productivity. In this context, seed tubes must be analyzed for their angular curvature. Thus, this study aimed to evaluate the influence of the seed tube curvature on the longitudinal distribution of corn and soybean seeds at different speeds. Two experiments were conducted completely randomized in a double factorial design. The first factor consisted of the seed tube curvature (straight and curved) and the second factor consisted of sowing speeds (1.11, 1.39, and 1.67 m s−1 for corn and 1.39, 1.67, 1.94, and 2.22 m s−1 for soybean), with five replications. The parameters analyzed to measure the longitudinal distribution were the number of seeds per meter, average spacing, double, flawed, and acceptable spacings, coefficient of variation, and precision index. The results were subjected to normality and homogeneity tests of residuals, followed by an analysis of variance and Tukey test, when significant. The curved seed tube showed the highest efficiency in the measured parameters for both corn and soybean. The increase in sowing speed had a negative influence on the evaluated parameters, especially in the soybean crop.